In-hospital Mortality in Patients with Low Haemoglobin Presenting with ST Elevated Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention - Haq, Ijaz Ul; Aslam, Uzair; Hamdani, Syed Hur Hussain; Yousuf, Shehla; Mahmood, Tayyab; Yousuf, Muhammad Usama (Indus Journal of Bioscience Research, 2025)
Objective: This study aimed to evaluate the impact of low haemoglobin levels on in-hospital mortality among patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI) at NICVD (National Institute of Cardiology) Karachi. Methodology: A retrospective observational study was conducted from May 17, 2023 to November 17, 2023, including 250 STEMI patients. Data on demographics, haemoglobin levels, comorbidities, and procedural outcomes were analyzed. The association between low haemoglobin and in-hospital mortality was assessed using chi-square tests, t-tests, and logistic regression models, with statistical significance set at p<0.05. Results: The study included 150 males (60%) and 100 females (40%) with a mean age of 58.4 years. The majority (84%) were diagnosed with STEMI, and 98% underwent PCI. Haemoglobin levels ranged from 7.0 to 11.0 g/dL. In-hospital mortality was 8% (20/250), significantly higher in patients with haemoglobin <8.0 g/dL. Mortality was associated with diabetes (p=0.04) and hypertension (p=0.01). PCI success significantly correlated with survival (p=0.001). Low haemoglobin levels were independently associated with increased mortality (p=0.02). Conclusion: Low haemoglobin significantly increases in-hospital mortality in STEMI patients undergoing PCI. Early screening and management of anaemia are essential to improve outcomes. Further prospective studies are recommended to validate these findings and explore interventional strategies.